Minimum geotechnical requirements for traditional and singular bridges foundations design: Chacao Suspension Bridge - Peña, Álvaro; Valenzuela, Matías; Márquez, Marcelo; Pinto, Hernán (Revista de la Construcción. Journal of Construction, 2017)
Bridges projects, usually considered a wide range of geotechnical research for the design of foundations. These works are of considerable importance for the proper design of foundations (shallow or deep) as well as to avoid problems during the project execution (time, cost, safety, complementary campaigns, etc.). This paper aims to analyze criteria and minimum geotechnical requirements for the project development of traditional and long-span bridges in Chile, taking into account international and national experience, considering as case of study the Project of Design and Construction of Chacao Bridge: multi-span suspension bridge with two main spans, 1,055 m and 1,155 m, currently underway in southern Chile, as a result of this work a summary of the minimum geotechnical requirements needed is proposed.